2019
DOI: 10.1111/cbdd.13469
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the selective mechanism of phosphoinositide 3‐kinase γ with benzothiazole and thiazolopiperidine γ‐specific inhibitors by in silico approaches

Abstract: The phosphoinositide 3‐kinase γ (PI3Kγ) has been verified to be a potential drug target for the treatments of various human physical disorders. Although received lots of attention, the development of PI3Kγ‐selective inhibitors is still a challenging subject because of its unique protein structural features. Aiming to uncover the interaction mechanism between the selective inhibitors and PI3Kγ, a series of benzothiazole and thiazolopiperidine PI3Kγ isoform‐selective inhibitors were studied with an integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…At last, a 30 ns NPT MD simulation was performed, using the SHAKE algorithm to bind all the bonds involving hydrogen and the time step was set to 2.0 fs. Coordinates were saved every 10 ps [35].…”
Section: Selective Inhibition Mechanisms Of Gsk3βmentioning
confidence: 99%
“…At last, a 30 ns NPT MD simulation was performed, using the SHAKE algorithm to bind all the bonds involving hydrogen and the time step was set to 2.0 fs. Coordinates were saved every 10 ps [35].…”
Section: Selective Inhibition Mechanisms Of Gsk3βmentioning
confidence: 99%
“…The inhibitors of this series had evolved from a reported pan‐PI3K inhibitor with a phenylthiazole core 34 . To uncover the SAR of these PI3Kγ‐selective inhibitors, Zhu et al 95 reported a theoretical study by utilizing multiple in silico methods including molecular docking, molecular dynamics (MD) simulations and binding free energy calculations (Figure 11). Initially, 40 compounds were docked into the ATP‐binding pocket of PI3Kγ using three different docking protocols: rigid receptor docking, induced‐fit docking, and quantum mechanics‐polarized ligand docking 96,97 .…”
Section: Structural Biology Of Pi3kγmentioning
confidence: 99%
“…The binding structures predicted by induced‐fit docking were analyzed by MD simulations, MM/GBSA binding free energy calculations, and free energy decomposition 98,99 . The SAR analysis could identify not only the residues vital for PI3Kγ binding, but also the residues that are important for PI3Kγ isoform selectivity 95 . Recently, this group reported another improved SAR model 39 .…”
Section: Structural Biology Of Pi3kγmentioning
confidence: 99%
“…ΔG GB was calculated by the Generalized Born (GB) model with the parameters developed by Onufriev et al (igb = 2); [43] ΔG GA was estimated based on the solventaccessible surface area (SASA) with a fast linear combination of the pairwise overlap (LCPO) algorithm using a probe radius of 1.4 Å: [44] ΔG SA = 0.0072 × ΔSASA; À TΔS the change of conformation entropy upon ligand binding would not be calculated here because of expensive computational cost and low prediction accuracy. [45][46][47][48][49] In the ΔG GB calculations, the exterior dielectric constant was set to 80, and the solute dielectric constant was set to 1. [50,51] All energy components were calculated using the MM_PBSA program of AMBER16 based on 5000 snapshots evenly extracted from 50 to 100 ns.…”
Section: Binding Free Energy Calculations and Decompositionmentioning
confidence: 99%